Factors associated to teenage pregnancy, an integrative review (Research, Society and Development, 2022)
Adolescent pregnancy is a public health problem in several countries, due to the high prevalence and the biological, social, psychological and economic consequences for both mother and child. This study aims to analyze the variables associated to adolescent pregnancy in Brazilian scientific productions. It is an integrative literature review from 2011 to 2020, using the LILACS and PubMed databases. Were included Brazilian studies hat analyzed factors related to adolescent pregnancy. Of the total, twenty-one articles were selected for analysis. In general, lower education, brown skin color, marital status (no partner), factors related to reproductive physiology or sexuality, alcohol or tobacco consumption, occupation, factors related to family and/or friends, and low socioeconomic conditions were factors associated with adolescent pregnancy. The results may contribute to the promotion of new public health policies, besides broadening discussions in the subject. We emphasize the importance of targeted actions towards adolescent health education, especially regarding communities in socioeconomic vulnerability.